Natural infection of phlebotomines (Diptera: Psychodidae) by Leishmania (Leishmania) amazonensis in an area of ecotourism in Central-Western Brazil. Issue 1 (December 2015) - Brilhante, Andreia; Nunes, Vânia; Kohatsu, Kleber; Galati, Eunice; Rocca, Maria; Ishikawa, Edna
Abstract Background Bonito municipality, known as an area of ecoturism, in Mato Grosso do Sul state, Brazil, is also a focus of visceral and cutaneous leishmaniases, with cases registered in both human and canine populations. This study sought to investigate natural infection by flagellate forms ofLeishmania in phlebotomines of the urban area of Bonito. Findings Sand flies were collected fortnightly from October 2005 to July 2006 with modified automatic light traps installed in peridomiciles and animal shelters in the center and on the outskirts of the city. The females were dissected and their guts observed under an optical microscope. A total of 1977 specimens were captured, Lutzomyia longipalpis (88.4 %) andBichromomyia flaviscutelata (3.0 %) being the most frequent species.Bi. flaviscutellata was found infected by flagellates that were identified asLeishmania (Leishmania) amazonensis by indirect immunofluorescence reaction, employing monoclonal antibodies and the biotin-avidin system. This is the first report of natural infection byL. amazonensis inBi. flaviscutellata in a Brazilian urban area. Conclusions AsBi. flaviscutellata is only slightly attracted by humans, the transmission ofL. amazonensis in the study area may have a zoonotic character; however, the sympatric occurrence of this parasite andLu. longipalpis should be taken into consideration by the local health authorities since this sand fly has already been found withL. amazonensis DNA in a focus of canine visceral leishmaniasis in Bonito municipality.